Decrease in Labor Levels in the Covid-19 Government Budget - Lesi Hertati; Wahyudin Zarkasy; Mohammad Adam; Haryono Umar; Harry Suharman (Ilomata International Journal of Tax and Accounting, 2020)
The overall budget of the government affected by covid-19 plays an important role in contributing to the welfare of the people who are being hit by a corona outbreak and more importantly is how the government's focus in determining the composition of the government budget itself. Determination of the composition of the government budget is a strategic plan to achieve the population safety targets of the covid-19 outbreak and at the same time to emphasize the human resource sectors because all residents are required to lockdown. The government budget component is related to the provision of basic food and health assistance in the regions and the provision of basic community needs such as free food and free health. Government budget allocations to the food and health sectors for free encourage an increase in the corona outbreak so that the population death rate decreases more broadly. A small enemy that is not visible to the naked eye but enough to stifle the economy and employment so that development is stalled in all directions, poverty rates increase, economic growth is paralyzed. The government is responsible for the allocated financial allocations for health and food for the residents of their respective countries. The availability of food is influenced by the availability of local government budget in providing government policies. Regions that have better regional income budgets compared to other regions will tend to have high levels of regional income budgets. Government expenditure is closely related to community life processes due to the co-19 pandemic as a result of the government's success in handling co-19 nationally or regionally. This research method is descriptive and verification method, the analysis tool is structural equation modeling (SEM, Lisrel). The results showed that the decline in labor affected the Government Budget Period of the Covid-19.